O impacto econômico da entrada da Vivo no mercado de telefonia móvel cearense - Gonçalves, Antonio Torquato Augusto (2013)
The Brazilian cell phone industry becomes increasingly successful in the late decades. Indeed, in Brazil the government is not the state-owned telecommunication monopoly. With the prominent introduction of the service into the ceareanse market in 1988, it has lured over 260 million telephone lines by late 2012. The four Brazilian´s dominant telecommunications companies are Vivo, Claro, Tim and Oi. Vivo is the national leader, though it operates in Ceara only recently. Vivo has tightened its grasp on the local phone market, as in consequence one intends to assess its results by means of Cournot model, which is related with the Lerner index. This one puts much greater emphasis on the market concentration and elasticity. To calculate the evolution in the remaining market, the Herfindahl-Hirschman index is applied, and to evaluate the market consistence, one considered Lerner index. Besides, we take a contrafactual test in which Vivo advantages are considered in isolation. Rather, the market force, after Vivo´s introduction, down from 10,69 per cent, while in face of contrafactual test, i.e, without Vivo, accounted for only 5,19 per cent. From the economics viewpoint, the difference between the real market and contrafactual was 5,5 per cent. The same research was done bearing in mind Piaui state, in order to compare how the company operated in another area. The economics gains was 22,27 per cent. This just shows the valuable gains issued from Vivo´s introduction in the two states.